Fig. 1 in First three-dimensional skull of the Middle Triassic mixosaurid ichthyosaur Phalarodon fraasi from Svalbard, Norway - Roberts, Aubrey Jane; Engelschiøn, Victoria Sjøholt; Hurum, Jørn Harald (Zenodo, 2022)
Fig. 1. Mixosaurid ichthyosaur Phalarodon fraasi (Merriam, 1910) PMO 235.393, from the Botneheia Formation, Middle Triassic of the Isfjorden area in Spitsbergen, Svalbard. A. Slab A in concretion, photograph (A1), line drawing (A2) showing the outline and identification of the visible bone elements. B. Hypothetical reconstruction of PMO 235.393. Published as part of Roberts, Aubrey Jane, Engelschiøn, Victoria Sjøholt & Hurum, Jørn Harald, 2022, First three-dimensional skull of the Middle Triassic mixosaurid ichthyosaur Phalarodon fraasi from Svalbard, Norway, pp. 51-62 in Acta Palaeontologica Polonica 67 (1) on page 53, DOI:10.4202/app.00915.2021, http://zenodo.org/record/10981077